PERAN KUALITAS KOLABORASI TEKNOLOGI BERBASIS PENGGUNAAN TEKNOLOGI MENUJU PENINGKATAN EFISIENSI KERJA DALAM KONTEKS PENGALAMAN PENGGUNAAN INFORMATION COMMUNICATION TECHNOLOGY - Ralin Ralin (Jurnal Riset Bisnis Indonesia, 2015)
The purpose of this research is to examine hypothesis in order to correct or strengthen it with the resultto strengthen theory underlying the topic. Research related to the topic used is explanatory research.This research took place in departement of agricultur and forestry jepara regency.The respondentsfor this research is amount of the 60 peoples and used sensus method as the sampling methodand program regression of SPSS 10.0 for windows as the data analysis.The result of hypothesisexamination show that: the higher intensity of technology use, the higher technological collaborationquality; the higher intensity of technology use, the higher work efficiency of human resources; thehigher technological collaboration quality, the higher work efficiency of human resources; the highertechnological collaboration quality, the higher the work efficiency of human resources with themoderation of ICT usage experience; the higher intensity of technology use, the higher the workefficiency of human resources with the moderation of ICT usage ecperience.Keywords: Work efficiency, Quality Of Collaboration Technologies, Use Of Technologies